2015
DOI: 10.1038/nrendo.2015.84
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric and metabolic surgery: a shift in eligibility and success criteria

Abstract: The obesity epidemic, combined with the lack of available and effective treatments for morbid obesity, is a scientific and public health priority. Worldwide, bariatric and metabolic surgeries are increasingly being performed to effectively aid weight loss in patients with severe obesity, as well as because of the favourable metabolic effects of the procedures. The positive effects of bariatric surgery, especially with respect to improvements in type 2 diabetes mellitus, have expanded the eligibility criteria f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
121
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(127 citation statements)
references
References 144 publications
(240 reference statements)
1
121
0
5
Order By: Relevance
“…Involvement with these innovations may have save time and money, improve existing preand post-operative bariatric surgical services, and engage with groups of patients who do not, or are unable to attend routine appointments, such as known DNAs and patients with mobility problems. Engagement with mobile apps and social media by patients, with the role of healthcare professionals in the latter clearly defined, there may also be opportunities for patients to be more actively involved in monitoring their progress after surgery, not just in terms of weight loss, but also diet, exercise and other aspects of general well-being, further broadening the perception of 'success' after surgery (17). The concerns and issues raised by AHPs with respect to the role of social media, mobile apps and technology in terms of adjuvant support tools for bariatric surgery should continue to be explored and evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Involvement with these innovations may have save time and money, improve existing preand post-operative bariatric surgical services, and engage with groups of patients who do not, or are unable to attend routine appointments, such as known DNAs and patients with mobility problems. Engagement with mobile apps and social media by patients, with the role of healthcare professionals in the latter clearly defined, there may also be opportunities for patients to be more actively involved in monitoring their progress after surgery, not just in terms of weight loss, but also diet, exercise and other aspects of general well-being, further broadening the perception of 'success' after surgery (17). The concerns and issues raised by AHPs with respect to the role of social media, mobile apps and technology in terms of adjuvant support tools for bariatric surgery should continue to be explored and evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…25 Bariatric surgery has been shown to be an effective treatment for weight loss. 26 However, different types of bariatric surgery carry individual risk of developing kidney stones as revealed in our meta-analysis. Although RYGB is considered as a mixed restrictive and malabsorptive procedure, standard RYGB (Roux-en-Y limb ¼150 cm) causes less malabsorption compared to very-long limb RYGB.…”
Section: Discussionmentioning
confidence: 99%
“…Although RYGB is considered as a mixed restrictive and malabsorptive procedure, standard RYGB (Roux-en-Y limb ¼150 cm) causes less malabsorption compared to very-long limb RYGB. 26,27 However, studies have still found significant hyperoxaluria in patients following Figure 1. Outline of our search methodology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the frequencies of using metformin and statin, which were known to increase preheparin LPL level [18, 31], became significantly lower in the LSG group than the nonsurgical group after 12 months, although the preheparin LPL level increased only significantly in the LSG group. Several reports have described that bariatric surgery (or metabolic surgery) improved obesity-related metabolic disorders, especially diabetes, beyond simple weight loss [32-34]. Some studies have suggested mechanisms involved in the beneficial effects of bariatric surgery on obesity-related metabolic disorders beyond simple weight loss.…”
Section: Discussionmentioning
confidence: 99%